SIMULATOR MODEL OF ORDER SERVICE SYSTEM OF THE COMMUNICATION OPERATOR BASED ON THE PETRI NET - V. P. Mochalov; S. V. Yakovlev; N. Y. Bratchenko (Современная наука и инновации)
The existing centralized systems for operational management of telecommunications do not fully comply with the requirements for new generation networks due to the limitations associated with the formation of new communication services, the flexibility and convenience of their modernization.